2016
DOI: 10.1051/0004-6361/201628465
|View full text |Cite
|
Sign up to set email alerts
|

Embedded star clusters as sources of high-energy cosmic rays

Abstract: Context. Massive stars are mainly found in stellar associations. These massive star clusters occur in the heart of giant molecular clouds. The strong stellar wind activity in these objects generates large bubbles and induces collective effects that could accelerate particles up to high energy and produce γ-rays. The best way to input an acceleration origin to the stellar wind interaction in massive stellar cluster is to observe young massive star clusters in which no supernova explosion has occurred yet. Aims.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…SFRs are thus expected to be sites of efficient cosmic-ray acceleration through different processes (Bykov 2014). Models include diffusive acceleration by the shockwaves of SNRs (Caprioli 2015) and by the termination shock of massive stellar winds (Lang et al 2005), as well as stochastic acceleration by the magnetic turbulence induced by all those shockwaves (Bykov & Toptygin 2001;Maurin et al 2016). The Cygnus Cocoon is the only SFR firmly associated with an extended γ-ray source seen by the LAT (Ackermann et al 2011).…”
Section: Crab Nebula (Fhesj05345+2201)mentioning
confidence: 99%
“…SFRs are thus expected to be sites of efficient cosmic-ray acceleration through different processes (Bykov 2014). Models include diffusive acceleration by the shockwaves of SNRs (Caprioli 2015) and by the termination shock of massive stellar winds (Lang et al 2005), as well as stochastic acceleration by the magnetic turbulence induced by all those shockwaves (Bykov & Toptygin 2001;Maurin et al 2016). The Cygnus Cocoon is the only SFR firmly associated with an extended γ-ray source seen by the LAT (Ackermann et al 2011).…”
Section: Crab Nebula (Fhesj05345+2201)mentioning
confidence: 99%
“…This would indicate that the particle acceleration in the Cygnus cocoon is not a special case and that other young massive SFRs have capabilities to accelerate particles via the same mechanism. However, a recent work by Maurin et al (2016) has shown that the H II regions powered by young stellar clusters such as the Rosetta and Orion Nebulae are not detected by the Fermi-LAT. This could be explained by the different bubble sizes; the G25 bubble and Cygnus cocoon are larger than the H II regions by more than an order of magnitude.…”
Section: Acceleration In Young Massive Sfrsmentioning
confidence: 99%
“…Notice, however, that the earlier census of a possible GeV emission from another sample of YMSCs did not lead to any significant gamma-ray signal (Maurin et al 2016). In that paper the authors analysed the Fermi telescope observations of YMSCs associated with the Rosette and Orion Nebulae (of luminosities below 10 37 erg s −1 ), NGC2175, NGC2467 and some others.…”
Section: Gamma Rays From Massive Star Clustersmentioning
confidence: 98%
“…The main damping process in HII regions is the turbulent damping (Farmer andGoldreich 2004, Lazarian 2016). We consider the following parameters: n g = 1000 cm −3 , the magnetic field B = 10 µG and gas temperature T ∼ 10 4 K (Maurin et al 2016 20 motions. The numerical modeling of this turbulence finds rms speed v t of the turbulent velocity of the order ∼ 10 km s −1 , slightly supersonic (Medina et al 2014).…”
Section: Supernova Remnants and Superbubblesmentioning
confidence: 99%